2017
DOI: 10.1002/adem.201700587
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Behavior, Dynamic Recrystallization, and Texture Evolution of Ti–22Al–25Nb Alloy

Abstract: The hot deformation behavior, dynamic recrystallization, and texture evolution of Ti-22Al-25Nb alloy in the temperature range of 950-1050 C and strain rate range of 0.001-1 s À1 is investigated by plane-strain compression testing on the Gleeble-3500 thermo-mechanical simulator. The results show that the flow stress decreases with the increase of temperature and decrease of strain rate. Besides, the flow curves appear a serrate oscillation at a strain rate of 0.1 s À1 for all the temperature ranges, which may r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In addition, the macroscopic flow behavior of alloys can effectively reflect the microscopic deformation mechanisms . Some studies have shown that the deformation mechanisms of Ti alloys are mainly dynamic recovery (DRV), dynamic recrystallization (DRX), platelet kinking/elongated, phase transformation, and dynamic globularization . Lin et al found that the higher dislocation density and obvious dislocation pileups can be noticed at the α/β interface, which induces the DRX nucleation of β grains at the α/β interface for a Ti‐55511 alloy with basket‐weave microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the macroscopic flow behavior of alloys can effectively reflect the microscopic deformation mechanisms . Some studies have shown that the deformation mechanisms of Ti alloys are mainly dynamic recovery (DRV), dynamic recrystallization (DRX), platelet kinking/elongated, phase transformation, and dynamic globularization . Lin et al found that the higher dislocation density and obvious dislocation pileups can be noticed at the α/β interface, which induces the DRX nucleation of β grains at the α/β interface for a Ti‐55511 alloy with basket‐weave microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…By the increase of the strain rate, the flow softening phenomenon was observed at low temperatures. Flow softening followed by a steady state flow stress is due to the occurrence of dynamic re- covery and dynamic recrystallization; whereas a continuous descending flow curve is a sign of flow localization resulted in cracks and adiabatic shear bands [27][28]. Such conditions may exist in specimens deformed at 850°C-950°C with strain rates around 0.1 s À 1 , and section 3.3 will discuss these possibilities.…”
Section: Flow Stress Curvesmentioning
confidence: 99%
“…[1][2][3][4][5] Currently, suitable hot deformation can effectively refine grains and improve the mechanical properties of titanium alloys. [6][7][8][9] Nevertheless, the hot deformation parameters observably affect the microstructure evolution and mechanical properties, and the processing windows are relatively narrow. [10][11][12] Therefore, it is necessary to research the flow behaviors and deformation mechanisms of titanium alloys.…”
Section: Introductionmentioning
confidence: 99%